Analysıs Of Factors That Influence Intentıon In Puchasıng Event That Improve Skılls In Batam’s Workforce - Renny Christiarini; Ory Dwiputra (Universitas Internasional Batam, 2021)
The purpose of this study is to find out what factors among purchase risk, purchase benefit & purchase value is most influence Batam citizens in purchasing events that enhance skills. This study uses non-probability sampling with a purposive sampling method with a total of 256 respondents and manages to find out the relationship between purchase benefit , purchase risk & purchase value have positive influence to the purchase intention and purchase benefit influence Batam citizens on purchasing event the most.